Effects of Coronavirus Fears on Anxiety and Depressive Disorder Symptoms in Clinical and Subclinical Adolescents: The Role of Negative Affect, Intolerance of Uncertainty, and Emotion Regulation Strategies - Sandín, Bonifacio; Espinosa, Victoria; Valiente, Rosa M.; García-Escalera, Julia; Schmitt, Julia C.; Arnáez, Sandra; Chorot, Paloma (Frontiers in Psychology, 2021)
Fears related to COVID-19 (“coronavirus fears”) have emerged as a new psychological effect of the current COVID-19 pandemic and have been associated with psychological distress and impairment. Other adverse effects include an increase in anxiety and depression symptoms and the respective disorders. The purpose of the current study was to examine the incremental validity of coronavirus fears and transdiagnostic factors in the prediction of the severity of anxiety and depressive disorder symptoms. A sample of 144 adolescents (aged 12-18 years) most of whom showed elevated levels of anxiety and depressive disorder symptoms completed several self-report measures online assessing coronavirus fears, transdiagnostic vulnerability and protective factors, and emotion regulation strategies. Results based on a series of hierarchical multiple regression analyses revealed that coronavirus fears, negative affect, intolerance of uncertainty, acceptance/tolerance, rumination and suppression explained unique variance in the severity of anxiety and depressive disorder symptoms. Path analysis demonstrated that acceptance/tolerance, rumination and suppression mediated the association between higher level transdiagnostic factors and the severity of major depressive disorder symptoms. Findings provide support for the hierarchical transdiagnostic model of emotional disorders (Sandín, Chorot et al., 2020) and suggest that clinicians should be aware of coronavirus fears. Also, the results warrant the need to consider transdiagnostic vulnerability and protective processes in the new protocols for the treatment of emotional disorders.